Formulation and In-vitro Evaluation of Microcrystalline Chitosan Based Buccoadhesive Bilayered Tablets of Repaglinide - Singh, Manoj K (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACT The buccoadhesive tablets of Repaglinide were prepared with the objective of avoiding the first pass metabolism as well as to evaluate the sustained release component of microcrystalline chitosan and compared with the carbopol. The buccoadhesive tablets were prepared by direct compression method using different composition of microcrystalline chitosan as a primary polymer, and secondary polymer like HPMC K4M, Sodium CMC and Karaya gum. The formulations were evaluated for the hardness, thickness, weight variation, content uniformity, surface pH, swelling index, in-vitro bioadhesion, in-vitro mucoadhesion retention time, in-vitro drug release kinetics. The modified physical balance was used to measure the in-vitro bioadhesion strength, using fresh goat buccal mucosa as a model tissue. The best mucoadhesive performance and in-vitro drug release profile were exhibited by the tablet containing microcrystalline chitosan and Sodium CMC in the ratio of 1:1. The mechanism and order of drug release from the tablets were non-Fickian diffusion (values of n between 0.5 to 1.0) and first order kinetics, respectively. The formulation containing 1:1 ratio of microcrystalline chitosan and Sodium CMC, showed good bioadhesion strength (33.21±4.48), mucoadhesion time (399±4.76) and controlled release property (95.3% after 8 h) as well as acceptable surface pH (5.9±0.4) to the buccal mucosa. The stability studies of buccoadhesive tablets were evaluated for their physico-chemical parameters such as colour, shape, thickness and drug contents which exhibit no changes, suggesting the satisfactory stability of buccal tablets in human saliva.